Social determinants associated with teenage pregnancy in the 24 de Mayo community in Ecuador - Barcia, José D.; Bravo, Alisson L.; Leones, Renata M.; Mendoza, Valeria I.; Veliz, Helen Z.; Cedeño, José A.; Batista, Reisey (Revista Gregoriana de Ciencias de la Salud, 2025)
Adolescent pregnancy is a significant public health concern with social, economic, and educational repercussions. This study aimed to describe the social determinants associated with teenage pregnancy in the 24 de Mayo community, Manabí, Ecuador. An observational, descriptive, and cross-sectional study was conducted from April to September 2023, during which surveys were administered to 30 community members to assess factors such as sexual education, family background, and contraceptive use. Results showed that 80% of respondents had a family history of adolescent pregnancy, 63.3% considered sexual education insufficient, and 90% did not use contraceptives. Early sexual initiation and limited institutional engagement were also observed. The study concludes that implementing educational strategies, enhancing access to comprehensive sexual education, and reinforcing family planning are essential to reduce the prevalence of adolescent pregnancy and its intergenerational consequences.